2021
DOI: 10.1080/23311975.2021.1959007
|View full text |Cite
|
Sign up to set email alerts
|

Examining the mediating-moderating role of psychological contract breach and abusive supervision on employee well-being in banking sector

Abstract: Previous research rarely examined the antecedents of employee wellbeing with the interactive effect of abusive supervision and mediating impact of psychological contract breach especially in the developing country context. Drawing upon the social exchange theory, this study attempts to bridge a research gap by investigating work engagement, work-life balance, and turnover intention with employee well-being directly and through the moderating and mediation effects of abusive supervision and psychological contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…The concept of the psychological contract has attracted attention mostly for two reasons; first, it is a way of understanding and managing the attitude and behaviours of employees within a company ( Agarwal et al, 2021 ); and secondly, it helps us understand how the relationship between employee and employer evolves ( Griep and Vantilborgh, 2018 ). A breach of a psychological contract occurs when either the employee or employer feels that the other party has not fulfilled a perceived expectation ( Gulzar et al, 2021 ). A breach of this contract can lead to either party feeling psychologically and emotionally aggrieved, therefore leading to a loss of loyalty, motivation, and overall, duty underperformance ( Gulzar et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of the psychological contract has attracted attention mostly for two reasons; first, it is a way of understanding and managing the attitude and behaviours of employees within a company ( Agarwal et al, 2021 ); and secondly, it helps us understand how the relationship between employee and employer evolves ( Griep and Vantilborgh, 2018 ). A breach of a psychological contract occurs when either the employee or employer feels that the other party has not fulfilled a perceived expectation ( Gulzar et al, 2021 ). A breach of this contract can lead to either party feeling psychologically and emotionally aggrieved, therefore leading to a loss of loyalty, motivation, and overall, duty underperformance ( Gulzar et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A breach of a psychological contract occurs when either the employee or employer feels that the other party has not fulfilled a perceived expectation ( Gulzar et al, 2021 ). A breach of this contract can lead to either party feeling psychologically and emotionally aggrieved, therefore leading to a loss of loyalty, motivation, and overall, duty underperformance ( Gulzar et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To fulfil the supervisors’ expectations, customer requirements, organizational targets and the repetitive and mundane nature of tasks, the employees undergo a lot of pressure (Wang and Wang, 2020). Additionally, supervisory abuse (Gulzar et al , 2021) and mistreatment such as ostracism (Wang et al , 2020) create harmful effects on an employee’s well-being. As per COR theory (Hobfoll, 1989), resilience acts as a possible cause of vigour (Davies et al , 2019) and permits an individual to remain energetic, engaged and involved in essential life chores even during difficult times (Hobfoll et al , 2018).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…On the other hand, several empirical studies reported that breaching a psychological contract is one of the primary reasons influencing workers' performance (Amoah et al, 2021;Gulzar et al, 2021;Said et al, 2021). The breach of a psychological contract occurs when the fulfillment of one of the obligations interferes with a psychological contract between employer and employee, which leads to adverse consequences influencing satisfaction and mutual trust (Jayaweera et al, 2021).…”
Section: Psychological Contract Fulfillmentmentioning
confidence: 99%